2009
DOI: 10.1128/iai.00965-08
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2 Deficiency Is Associated with Enhanced Severity of Group B Streptococcal Disease

Abstract: Group B streptococcus (GBS) has been recognized as an ever-growing cause of serious invasive infections in nonpregnant adults, in particular, in association with severe underlying diseases. The most common manifestations include primary bacteremia, urinary tract infections, pneumonia, meningitis, peritonitis, and osteoarticular infections. Toll-like receptor-2 (TLR2) mediates host responses to gram-positive bacteria. TLR2 function was investigated in murine GBS-induced sepsis and arthritis in wild-type (wt) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
(45 reference statements)
1
14
0
Order By: Relevance
“…Furthermore GBS can trigger microglial apoptosis in a pathway dependent upon TLR2 and caspase 8 [101]. A functional interaction between TLR2 and GBS is consistent with other studies which indicate that TLR2 is required for host defence against GBS in other disease settings such as arthritis and sepsis [102].…”
Section: Tlrs In Response To Bacterial Meningitissupporting
confidence: 88%
“…Furthermore GBS can trigger microglial apoptosis in a pathway dependent upon TLR2 and caspase 8 [101]. A functional interaction between TLR2 and GBS is consistent with other studies which indicate that TLR2 is required for host defence against GBS in other disease settings such as arthritis and sepsis [102].…”
Section: Tlrs In Response To Bacterial Meningitissupporting
confidence: 88%
“…3 A and B). Of note, we found that TLR2 KO BMDM secreted increased amounts of MIP-1α, MIP-1β, and monocyte chemoattractant protein-1 (MCP-1) in response to the ER stressconditioned medium relative to WT BMDM, suggesting that TLR2 may normally function as a negative regulator in response to proinflammatory stimuli (22,23). Next, we turned our attention to the IL-6R based on the following: (i) both cancer cells and macrophages secrete IL-6, a proliferative antiapoptotic proinflammatory cytokine; (ii) IL-6 production can be amplified by autocrine/paracrine mechanisms via IL-6 receptor (IL-6R) signaling (2); and (iii) the supernatant of LLC cells up-regulates IL-6 production in myeloid cells (6).…”
Section: Resultsmentioning
confidence: 87%
“…Next, we evaluated the impact of endotoxin tolerance on group B Streptococcus (GBS)-induced multifocal septic arthritis, a condition in which functional TLR2 signaling is necessary for attenuating the severity of group B streptococcal disease 33 . Mice preconditioned as in the Salmonella model were infected i.v.…”
Section: Resultsmentioning
confidence: 99%
“…Morphological investigation the lungs, livers and ceca of mice treated with different doses of LPS or l -kynurenine were as described 33 , and so were measurements of IDO1 functional activity in terms of l -kynurenine production 18 . In Fig.…”
Section: Methodsmentioning
confidence: 99%